Mechanical, aspiration and intra-arterial thrombectomy. First case in a patient with an acute stroke in a hospital - Saal-Zapata, Giancarlo (2020)
Acute stroke is one of the most common causes of morbidity and mortality worldwide. Mechanical thrombectomy is the endovascular procedure that has shown better results in patients with a large vessel involvement. We present here a case of a patient who had a five-hour history of thrombosis of the left middle cerebral artery who developed mixed aphasia and hemiparesis, ASPECTS scale of five, NIHSS score of 14 and a modified Rankin scale (mRS) of 4. A mechanical thrombectomy was performed with stents Solitaire AB and ERIC and manual aspiration of the clot with a 60cc syringe plus instillation of intra-arterial alteplase. Immediate reperfusion was complete (TICI 3). The mRS after the procedure was 2.